2020
DOI: 10.3390/jcm9051592
|View full text |Cite
|
Sign up to set email alerts
|

Pentaglobin® Efficacy in Reducing the Incidence of Sepsis and Transplant-Related Mortality in Pediatric Patients Undergoing Hematopoietic Stem Cell Transplantation: A Retrospective Study

Abstract: The 12-month mortality rate in patients undergoing hematopoietic stem cell transplantation (HSCT) remains high, especially with respect to transplant-related mortality (TRM), which includes mortality due to infection complications through the aplasia phase. The aim of this study was to determine whether the administration of Pentaglobin® could decrease TRM by lowering sepsis onset or weakening sepsis through the aplasia phase. One hundred and ninety-nine pediatric patients who had undergone HSCT were enrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Our results are consistent with those reported by Carlone et al who found that the adjuvant therapy with HT-IgM in pediatric HSCT patients was associated with a significant reduction of infection-related mortality rate. 33 Furthermore, they also found a decrease in days of fever, number of antibiotics used to control infections, number of antibiotic therapy changes, and a lower incidence of relapsing febrile episodes during a 6-month follow-up. 33 A randomized controlled trial, performed in a pediatric intensive care setting, showed that the use of polyclonal HT-IgM as an adjuvant in the management of sepsis led to a significant reduction in mortality, length of stay, and occurrence of complications, especially disseminated intravascular coagulation.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our results are consistent with those reported by Carlone et al who found that the adjuvant therapy with HT-IgM in pediatric HSCT patients was associated with a significant reduction of infection-related mortality rate. 33 Furthermore, they also found a decrease in days of fever, number of antibiotics used to control infections, number of antibiotic therapy changes, and a lower incidence of relapsing febrile episodes during a 6-month follow-up. 33 A randomized controlled trial, performed in a pediatric intensive care setting, showed that the use of polyclonal HT-IgM as an adjuvant in the management of sepsis led to a significant reduction in mortality, length of stay, and occurrence of complications, especially disseminated intravascular coagulation.…”
Section: Discussionmentioning
confidence: 92%
“…33 Furthermore, they also found a decrease in days of fever, number of antibiotics used to control infections, number of antibiotic therapy changes, and a lower incidence of relapsing febrile episodes during a 6-month follow-up. 33 A randomized controlled trial, performed in a pediatric intensive care setting, showed that the use of polyclonal HT-IgM as an adjuvant in the management of sepsis led to a significant reduction in mortality, length of stay, and occurrence of complications, especially disseminated intravascular coagulation. 34 Despite some limitations, such as the retrospective design, the limited number of analyzed cases and the lack of control groups, this study suggests that the use of HT-IgM deserves further prospective investigation.…”
Section: Discussionmentioning
confidence: 92%
“…IgM and IgA enriched immunoglobulin G has been successfully used for many years in the prophylaxis and treatment of severe sepsis and septic shock [ 13 , 24 , 25 , 26 , 27 ], particularly caused by Gram-negative bacteria [ 28 ]. A recent meta-analysis reported a reduction in mortality and ventilation time with the use of IgM and IgA enriched immunoglobulin G in patients with sepsis or septic shock compared with the respective control groups (relative risk (RR) 0.60) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indications for HSCT conformed to the American Society for Blood and Marrow Transplantation (ASBMT) task force recommendations for pediatric patients 17 . All patients who underwent allogeneic HSCT were treated according to standard myeloablative protocols, as previously described in the literature 18 . High‐dose posttransplantation cyclophosphamide‐based platforms were administered to all haploidentical recipients so that composite endpoints across conditioning intensity, donor type and HLA match were comparable 19 …”
Section: Methodsmentioning
confidence: 99%